2017
DOI: 10.1117/12.2253706
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nonlinear pulse propagation, Raman frequency conversion and near octave spanning supercontinuum generation in atmospheric air-filled hollow-core Kagomé fiber

Abstract: We have demonstrated Raman frequency conversion and supercontinuum light generation in a hollow core Kagomé fiber filled with air at atmospheric pressure, and developed a numerical model able to explain the results with good accuracy. A solid-state disk laser was used to launch short pulses (~6ps) at 1030nm into an in-house fabricated hollow core Kagomé fiber with negative core curvature and both ends were open to the atmosphere. The fiber had a 150 THz wide transmission window and a record low loss of ~12 dB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…This reveals that the Raman comb dynamics do not imply significant loss. Finally, the comb structure of the spectrum shows an insignificant to zero effect from Kerr nonlinearity, even at energy value as high as 1.03 mJ, which contrasts with those obtained with 6 ps [31].…”
Section: A Raman Comb Generationcontrasting
confidence: 80%
“…This reveals that the Raman comb dynamics do not imply significant loss. Finally, the comb structure of the spectrum shows an insignificant to zero effect from Kerr nonlinearity, even at energy value as high as 1.03 mJ, which contrasts with those obtained with 6 ps [31].…”
Section: A Raman Comb Generationcontrasting
confidence: 80%
“…Experimentally, simply using an air-filled broadbandguiding HC-PCF, Mousavi et al (2017) demonstrated a variety of nonlinear effects, including supercontinuum formation between 850 to 1600 nm, when pumping at 1030 nm. A more exotic supercontinuum mechanism based on the dispersion caused by the resonances in a broadband-guiding HC-PCF has also recently been reported (Sollapur et al, 2017), leading to broadening extending from 200 nm to 1.7 μm.…”
Section: J Near-infrared and Mid-infrared Supercontinuum Generationsmentioning
confidence: 99%